Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Mozambique Country Strategy Paper 2018 -2022. Supporting Mozambique towards the HIGH5s - Santos, Almeida (African Development Bank, 2018)
The African Development Bank Group’s Country Strategy Paper (CSP) 2018-22 for Mozambique comes at a time when the country adopted its long term development strategy ‘ENDE’ 2015-35. The CSP was prepared on the basis of extensive consultations held with the Government of Mozambique, Development Partners, the private sector and the civil society. The main objective of the ENDE is the improvement of the livelihoods of the population through the structural transformation of the economy, and the expansion and diversification of national production. The strategy is to be implemented through the 5-Year Government Programs (PQGs). The PQG goal for 2015-19 is to increase employment, productivity and competitiveness to improve living conditions of Mozambicans, in an environment of peace, harmony and tranquillity, while consolidating democracy and inclusive participatory governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (IESE Conference - Challenges of social and economic research in times of crisis, 2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (NUPI political economy reports, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Mozambique: Report 8/2016 Country Evaluation Brief - Tvedten, Inge; Orre, Aslak (Norwegian Agency for Development Cooperation (Norad), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Government Decentralization Program in Indonesia - Nasution, Anwar (ADBI, 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Social protection reform in Mozambique and the new basic social security strategy - Falange, Sergio; Pellerano, Luca (IPC-IG One Pager, 2016)
In the framework of efforts to fight extreme poverty and recognising the importance and need to protect the poor and vulnerable population, in 2007 Mozambique approved Law No. 4/2007 which structured social protection into three levels, including basic social security. In 2010 the first National Basic Social Security Strategy (ENSSB I) was approved for the period 2010–2014, including a set of old (e.g. the Basic Social Security Programme—PSSB) and new (e.g. the Productive Social Action Programme—PASP) non-contributory social protection programmes, all implemented by the National Institute for Social Action (INAS) under the policy guidance of the Ministry of Gender, Child and Social Action (MGCAS).
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

An Analysis of Mozambique’s Political and Economic Networks - Chivangue, Andes; Cortez, Edson (CEsA - research center part of CSG/Research in Social Sciences and Management, 2015)
This paper analyses the social networks existing among politicians and economists in contemporary Mozambique, using the SNA-Social Networks Analysis method to identify the links between these individuals, to discern their relationships and to measure both the density and the centrality of the political-business network. Mozambique’s political and business elite is thus identified. A network sociogram is presented identifying the individual position in the network and the linkages among these individuals and several positional metrics of the individuals in the network are estimated, allowing identifying each individual and its influence in the network. As this network is resource accumulation driven, this exercise permits to identify the main political and economic individual active in Mozambique economy. President Guebuza define the major network centre and other individuals, Joaquim Chissano, the former president, and Graça Machel, the widow of another former president. Policy implications are derived and the links between them displayed, allowing for an accurate view of Mozambique’s political and business world.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Gender in Political Economy Analysis - Browne, Evie (GSDRC, University of Birmingham, 2014)
This report provides a brief examination of how and where gender analysis is incorporated into Political Economy Analysis (PEA). An initial review of the literature indicates that gender is not systematically included in PEA. This was also conveyed by a number of experts consulted for this report, who stated that few if any PEAs to their knowledge had included a gender analysis, with the issue usually treated only in passing. The report nevertheless highlights the existing examples of gender-oriented analytical questions used in common PEA tools. It also identifies areas of overlap between gender and political economy analysis.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); gender / género

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil

Ten years of single window implementation: lessons learned for the future - Koh, Jonathan (Global Trade Facilitation Conference 2011, 2011)
This paper examines the Single Window concept and its developments in practice over the last 10 years and provides an analysis of its development over time. An overview of the emerging information technology that would impact its future development is also presented. The paper also examines regional trends in Single Window implementation, based on a survey of tenders documents issued by various countries in the recent years. Finally, it offers an outlook on its future development and provides a number of recommendations.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Local economic governance: a survey of business operators in 245 districts/municipalities in Indonesia, 2011 - The Asia Foundation; Regional Autonomy Watch (Local Economic Governance, 2011)
Decentralization has been underway in Indonesia for more than ten years, but recently many have challenged the how effectively decentralization – and even democratization – is being implemented. Deterioration in the quality of public services, the many corruption cases involving local governments, and low economic growth rates in some regions have prompted discourse about whether the country is making a reversal away from decentralization and democratization. We recognize that the move toward regional autonomy has not been without its faults. Nevertheless, a choice was made to strengthen democracy and move towards local autonomy based on the problems created by the centralistic, authoritarian system of the previous regime. Yet it is unfair to judge regional autonomy a failure after it has been implemented for such a short time, and under a somewhat inconsistent policy framework. Since 2001, the Regional Autonomy Watch (KPPOD) and The Asia Foundation have aimed to present a clear picture of the quality of regional economic governance from the perspective of business owners. Our studies provide input to government at the central, provincial and regional/municipal levels, as well as information to other stakeholders regarding efforts that can be undertaken to promote improve economic growth under regional autonomy. This year’s study finds significant variation among regions in the quality of economic governance. This indicates that despite many limitations, some regions have used the opportunities provided by autonomy to foster good governance while others have not. It is hoped that this present study, and the awards presented to regencies and municipalities with the best performance, will promote a healthy competition among regional leaders. It is also envisioned that local governments whose performance is still low can learn from their neighbors who are doing better, and be inspired to improve. We recognize that improving economic governance requires a strong commitment and hard work, not only from the heads of regions but from all ranks of government officials, politicians, business owners and other stakeholders. This study can help set priorities for reform of local economic governance, identifying areas for immediate improvement that are relatively easy to achieve but have the potential of significant impact. Other aspects may need more time for improvement.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; M - survey / inquérito; Northern PEA; decentralization / descentralização

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género